PERAN ORANG TUA DALAM MENGEMBANGKAN KEBIASAAN BELAJAR ANAK KELAS TINGGI DI SD N 16 LUHAK NAN DUO DESA SARIAK KECAMATAN LUHAK NAN DUO KABUPATEN PASAMAN BARAT - Yanti, Rahayu Fitri (Bimbingan dan Konseling, 2014)
In this reasearch is designed by the researcher, because parentsâ roles in developing of pupilsâ habit in study still weak and it effects toward pupils achievement. The aims of this research to analyze of : 1) giving pupilsâ facilities in study. 2) developing pupilsâ habit in study alone. Design of this research is quantiitative descriptive. Population of this research are 101 pupils. Technique of collecting population that is used by researcher is simple random sampling with the total sample 50 pupils. Technique of data collection is percentage technique. The result of this research, the researcher found that: 1) parentsâ roles in giving facilities in study are good it can be seen as: a) parents give study place, b) parents give school equipment, c) parents give transportation and finansial. 2) parentsâ roles in developing pupilsâ study alone was categorized good enough such as: a) guiding pupilsâ in study, b) giving a time to guide the pupils in study, c) helping the studen is in discussing the material, d) controling pupilsâ time and way in study, e) housing atmosphere that calm in studying, f) comunicating with pupil.